2019
DOI: 10.1111/scs.12749
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between breastfeeding attitudes and perceived stress levels of Turkish mothers

Abstract: Scand J Caring Sci; 2020; 34: 456-463 The relationship between breastfeeding attitudes and perceived stress levels of Turkish mothers Aims: In the present study, it was aimed to investigate the relationships between breastfeeding attitude and perceived stress levels of Turkish mothers. Methods: In this descriptive study, the Personal Information Form prepared by the researchers, Perceived Stress Scale (PSS) and Iowa Infant Feeding Attitude Scale (IIFAS) were used to collect the study data. The present study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
6
1
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 23 publications
4
6
1
3
Order By: Relevance
“…Symptoms of depression were negatively associated with breastfeeding attitude and self-efficacy, and symptoms of stress were negatively associated with self-efficacy. These results align with the international literature that has found that postnatal mental health can have a negative impact on breastfeeding beliefs (20)(21)(22)(23)(24).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Symptoms of depression were negatively associated with breastfeeding attitude and self-efficacy, and symptoms of stress were negatively associated with self-efficacy. These results align with the international literature that has found that postnatal mental health can have a negative impact on breastfeeding beliefs (20)(21)(22)(23)(24).…”
Section: Discussionsupporting
confidence: 91%
“…Maternal depression and anxiety have been found to be associated with lower breastfeeding self-efficacy (20)(21)(22). Maternal depression and stress have also been shown to be associated with less favorable attitudes towards breastfeeding (23,24), such as being more skeptical or unsupportive of the practice (25). Having a positive attitude about breastfeeding is important since breastfeeding beliefs have been shown to not only be associated with higher rates of exclusive breastfeeding (25)(26)(27)(28), but also other measures of breastfeeding outcomes, such as the duration the infant is breastfed (27)(28)(29), and the mother's satisfaction with breastfeeding (30).…”
Section: Introductionmentioning
confidence: 99%
“…Our study showed that exclusively breastfeeding mothers had lower PSS-10 scores than mothers who practiced mixed feeding. This result supports those of previous studies, which revealed that breastfeeding mothers showed significantly less perceived stress than mothers who bottle fed (Duran, Kaynak, & Karadaş, 2020;Mezzacappa, Guethlein, & Katkin, 2002). Groër (2005) revealed that breastfeeding mothers have more positive mood and lower perceived stress than those using artificial nutrition.…”
Section: Relationship Between Breastfeeding and Perceived Stresssupporting
confidence: 90%
“…Um estudo recente avaliou a relação entre o estresse da mãe e a amamentação e demonstrou que o ato ou a atitude de amamentar diminui à medida que o estresse percebido pela mãe aumenta. Sendo assim, as mães devem aprender estratégias sobre como lidar com o estresse, a fim de melhorar seu engajamento em relação à amamentação, e que serviços de aconselhamento devem ser iniciados no pré-natal, a fim de incentivá-las a amamentar (DURAN;KAYNAK;KARADAS, 2019).…”
Section: Discussionunclassified